Peminggiran tulisan Jawi sebagai lambang jati diri Melayu: satu kajian tinjauan - Abdullah, Zurina; Abdul Aziz, Adi Yasran (Penerbit KUIS, 2020)
This paper presents a case study discussion on Jawi scriptas as a symbol of Malay identity which is seen abandoned. In the discussion, abandonmentof Jawi script will be linked with research findings done by several researchers on youngsters and teenangers from school and higher learing instutuitions. Literature review indicated that mastery level of Jawi script among youth is still satisfactory especially in reading and writing skills. This is saddened as Jawi script is a powerful tool in knowledge expansion ofMalay world especially durimg the expansion of Malay classicalera around 13th to 19th centuary. However, post colonisation and independence of Tanah Melayu had seen Jawi script to be deteriorating which resulted in abandonment. In addition, Rumi script was gazetted as the official national writing script under National Language Act 1963.Hence, the purpose behind the emergence of this issue is to show to people that abandoning Jawi scriptis serious and and needs to be put into thoughts so that this treasure will not go missing butmustbe preservedespecially by the younger generations. The discussion also presents efforts done and suggested efforts that should be madeto ensure Jawi script will no longer be abandoned. In conclusion, the triumphof Jawi script as prestigious writing script will be reverted in conveying many different knowlegde fields.